2021
DOI: 10.20481/kscdp.2021.8.4.221
|View full text |Cite
|
Sign up to set email alerts
|

Hidden Markov Model(HMM)-Based Fishing Activity Prediction Using V-Pass Data

Abstract: Illegal fishing has been a serious threat to the conservation of seafood resources and provoked the importance of marine surveillance. There are several types of fishing vessel monitoring systems operated by Republic of Korea, for example, Vessel Monitoring System(VMS), Automatic Identification System (AIS), V-Pass and VHF-DSC. However, those methods are not adaptable directly to fishing activity monitoring. The limitation requires more human resources to determine fishing status. Thus, this study proposes a m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 14 publications
0
0
0
Order By: Relevance
“…For instance, a method for detecting the two most dangerous abnormal behaviors based on AIS was conducted in [14], a study establishing a major ship navigation route between ports based on the extracted ship orbiter cluster was conducted in [15], and a study suggesting a data preparation process for managing actual kinematic data and detecting fishing boats was conducted in [16]. Most studies on V-pass terminals used in most fishing boats focus only on V-pass data utilization; thus, few studies on the location accuracy-a crucial variableexist [17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, a method for detecting the two most dangerous abnormal behaviors based on AIS was conducted in [14], a study establishing a major ship navigation route between ports based on the extracted ship orbiter cluster was conducted in [15], and a study suggesting a data preparation process for managing actual kinematic data and detecting fishing boats was conducted in [16]. Most studies on V-pass terminals used in most fishing boats focus only on V-pass data utilization; thus, few studies on the location accuracy-a crucial variableexist [17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…Notably, no prior research has been conducted to validate the location accuracy of V-pass terminals, and the current research on the tracking data and system is limited, except for certain studies reported in the literature [4][5][6][7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%